2012
DOI: 10.1007/s11250-012-0085-5
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of bovine tuberculosis in Somali pastoral livestock, southeast Ethiopia

Abstract: A cross-sectional study of bovine tuberculosis (BTB) detected by the comparative intradermal tuberculin test (CIDT) was conducted in livestock of the Somali region in southeast Ethiopia—in four pastoral associations from January to August 2009. In 94 herds, each of 15 cattle, camels, and goats was tested per herd leading to a total of 1,418 CIDT tested animals, with 421 cattle, 479 camels, and 518 goats. A herd was considered positive if it had at least one reactor. Prevalence per animal species was calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 31 publications
3
47
4
Order By: Relevance
“…The current animal level BTB prevalence of 3.55% at ?_2 mm cut-off is comparable to the previously reported prevalence of 3.0% and 4.02% by other studies in different sites of Ethiopia (Tschopp et al , 2009;Firaol Tamiru et al, 2013) but significantly lower than the previously reported prevalence of 7.0% in southern Ethiopia (Balako Gumi et al, 2011), 18% in Afar (Gezahegne Mamo et al, 2013) and 6.8% Meskan, Gurage region, central Ethiopia (Tschopp et al, 2011). Animal prevalence of 1.27% recorded at ?_4mm cut-off value was similar to the prevalence of 2.0%, 1.0% and 1.56% in Ethiopia (Balako Gumi et al, 2012;Firaol Tamiru et al, 2013;Petros Admasu et al, 2014) and 2.6% in Zambia (Pandey et al, 2013) while it was lower than 11.0%, 23.7%, 5.5%, 30.0%, 11.0%, 4.3% and 11.3% in Ethiopia (Gobena Ameni and Erkihun Aklilu, 2007;Elias Kebede et al, 2008;Gumi et al, 2011;Rebuma Firdessa et al, 2012;Gezahegne Mamo et al, 2013;Gebremedhin Romha et al, 2014;Fikre Zeru et al, 2014), 7.13% in Ecuador (Proano-Perez et al, 2009, 14.3% in India (Thakur et al, 2010) and 5.9% in Bangladesh (Mondal et al, 2014). The variation observed among the studies might be attributed to differences in management practices, production system, types of cattle breeds largely involved in the study, or differences in ecological zones.…”
Section: Discussionsupporting
confidence: 76%
“…The current animal level BTB prevalence of 3.55% at ?_2 mm cut-off is comparable to the previously reported prevalence of 3.0% and 4.02% by other studies in different sites of Ethiopia (Tschopp et al , 2009;Firaol Tamiru et al, 2013) but significantly lower than the previously reported prevalence of 7.0% in southern Ethiopia (Balako Gumi et al, 2011), 18% in Afar (Gezahegne Mamo et al, 2013) and 6.8% Meskan, Gurage region, central Ethiopia (Tschopp et al, 2011). Animal prevalence of 1.27% recorded at ?_4mm cut-off value was similar to the prevalence of 2.0%, 1.0% and 1.56% in Ethiopia (Balako Gumi et al, 2012;Firaol Tamiru et al, 2013;Petros Admasu et al, 2014) and 2.6% in Zambia (Pandey et al, 2013) while it was lower than 11.0%, 23.7%, 5.5%, 30.0%, 11.0%, 4.3% and 11.3% in Ethiopia (Gobena Ameni and Erkihun Aklilu, 2007;Elias Kebede et al, 2008;Gumi et al, 2011;Rebuma Firdessa et al, 2012;Gezahegne Mamo et al, 2013;Gebremedhin Romha et al, 2014;Fikre Zeru et al, 2014), 7.13% in Ecuador (Proano-Perez et al, 2009, 14.3% in India (Thakur et al, 2010) and 5.9% in Bangladesh (Mondal et al, 2014). The variation observed among the studies might be attributed to differences in management practices, production system, types of cattle breeds largely involved in the study, or differences in ecological zones.…”
Section: Discussionsupporting
confidence: 76%
“…But it is higher than the reports of Mamo et al (2009) at Dire Dawa, and Gumi et al (2011) in Southern Ethiopia. Similarly, it is significantly higher than previously reported prevalence of some other authors at different sites in Ethiopia (Gumi et al, 2011(Gumi et al, , 2012Tamiru et al, 2013;Admasu et al, 2014;Ameni and Aklilu, 2007;Romha et al, 2014;Nuru et al, 2015), in Zambia (Pandey et al, 2013), in Ecuador (Proano-Perez et al, 2009) in Bangladesh (Mondal et al, 2014).…”
Section: Discussionmentioning
confidence: 51%
“…It is mostly seen as latent infection, whereas the clinical signs are not specifically differential, these includes anorexia, weakness, dyspnea, enlargement of lymph nodes and emaciation. In dead animals, disease may diagnose through histopathological techniques, necropsy and culture, while in live animals delayed hypersensitivity is widely using tool to diagnose the infection however, this approach is not considered reliable due to some fraction of false positive results (Gumi et al, 2012). Bovine tuberculosis is an endemic disease of cattle and buffaloes in Pakistan ( Jalil et al, 2003).…”
Section: Discussionmentioning
confidence: 99%